Evaluation proposal of a national community-based obesity prevention programme: a novel approach considering the complexity perspective - Irma Huiberts; Amika Singh; Frank J. van Lenthe; Mai Chinapaw; Dorine Collard (BMC, 2022)
Abstract Community-based obesity prevention programmes are considered an important strategy to curb the obesity epidemic. The JOGG (Youth At a Healthy Weight) approach is a large-scale community-based programme for childhood obesity prevention in the Netherlands that has been implemented over the past ten years. Practice-based development of the programme, both at the national and local level, increasingly poses challenges for its evaluation. One considerable challenge is the increasing acknowledgement of the complexity in the JOGG-approach, characterized by (a) objectives that vary locally, (b) adaptions to the programme over time in response to a community's shifting needs, challenges and opportunities, and (c) emergent outcomes and non-linear causality. We propose an evaluation framework that highlights elements of the complex local practice, including the local programme theory, implementation, adaption, the influence of context and feedback loops and intended as well as emergent and unintended outcomes. By studying each of these elements in practice, we hope to learn about principles that guide effective obesity prevention across contexts. The results of the proposed evaluation will inform both practice and research. Considering complexity in evaluation is a relatively new challenge in public health and therefore an emergent research area. The proposed framework for complex evaluations allows to retrospectively evaluate a programme that was implemented and developed in practice, and enables us to learn from practice-based experiences. Following the ISBNPA Dare2Share initiative, we kindly invite other researchers in the field to share their ideas and experiences regarding integration of complexity in evaluation.